2021
DOI: 10.21203/rs.3.rs-192581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SLC7A5 Promotes Colorectal Cancer Progression by Regulating Cell Cycle and Migration

Abstract: Background: Solute carrier family 7 member 5 (SLC7A5) was identified highly expressed and as a key participant in various tumor development; however, the role it played in colorectal cancer remains unclear. Methods and Results: In the current study, the expression of SLC7A5 were systematically mined in public databases and validated by real-time PCR in colon cancer and normal tissues. And then, the co-expression and pathway analysis got from public database, which indicated the potential influence of SLC7A5 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The protein Q6YN16 (hydroxysteroid dehydrogenase-like protein 2 -HSDL2) is involved in fatty acid metabolism and is well associated with the progression of various types of cancer. 45,46 For example, it has been shown that in various types of gliomas, overexpression of this protein induces proliferation and increases cell survival, while gene knockdown leads to apoptosis and cell cycle arrest. 47 In contrast to the previous study, a recent report demonstrated that knockdown of HSDL2 led to inhibition of ferroptosis in cholangiocarcinoma cells, thereby promoting cancer progression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The protein Q6YN16 (hydroxysteroid dehydrogenase-like protein 2 -HSDL2) is involved in fatty acid metabolism and is well associated with the progression of various types of cancer. 45,46 For example, it has been shown that in various types of gliomas, overexpression of this protein induces proliferation and increases cell survival, while gene knockdown leads to apoptosis and cell cycle arrest. 47 In contrast to the previous study, a recent report demonstrated that knockdown of HSDL2 led to inhibition of ferroptosis in cholangiocarcinoma cells, thereby promoting cancer progression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Glutamine is required to produce glutathione that removes ROS and rescues the cancer cells from oxidative stress-induced apoptosis since ROS is produced by cancer cells due to an increased metabolic rate, gene mutation, and relative hypoxia [39]. Moreover, BCAAs are utilized to synthesize glutamate and glutathione and lead to therapeutic resistances following overexpression of SLC7A5, a BCAA transporter observed in pancreatic, colorectal, gastric, and OC cells [40][41][42]. Therefore, OC patients with stage IV may be highly Myc-driven and then overexpressed ASCT2 and SLC7A5 to promote glutamine homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of SLC7A5 , SLC9A3 , ABCC2 , ABCG2 , etc. in the invasion and progression of CRC has been reported. Nevertheless, current research on the molecular mechanisms by which these transporters impact CRC, as well as their potential application as drug targets in clinical treatment, remains insufficient. Here, we performed a comprehensive bioinformatics analysis to identify differentially expressed transporter protein-related genes (DE-TPRGs) in CRC and determine their potential functions involved in CRC progression.…”
Section: Introductionmentioning
confidence: 99%